ANALISIS PENGARUH PENANAMAN MODAL ASING DAN PENANAMAN MODAL DALAM NEGERI TERHADAP PERTUMBUHAN EKONOMI PADA 6 PROVINSI DI PULAU JAWA (2017-2021) - TERESA MAITRIDANI,; HANA SYAFIRA,; SATRIA MAULANA YUSUF,; REGGY PANGESTU NURDIANSYAH, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2023)
This study aims to analyze the effect of Foreign Investment and Domestic Investment on economic growth in 6 provinces on the island of Java. The data used is time series data from the year 2017 to 2022. Data were analyzed using the method with the help of Eviews version 12. The results showed that Foreign Investment (PMA) and Domestic Investment (PMDN) have a significant influence on economic growth both in the short and long term.